Photocatalytic Degradation of Amoxicillin Using UV/Synthesized NiO from Pharmaceutical Wastewater - Davoud Balarak; Ferdos Kord Mostafapour (Universitas Gadjah Mada, 2019)
The nano nickel(II) oxide (NiO) was synthesized by sol-gel method and used for degradation of Amoxicillin (AMO) from pharmaceutical wastewater. In this laboratory study, the effects of nanoparticle dose (0.25–2 g/L), reaction time (10–120 min), initial antibiotic concentration (25–200 mg/L) and lamp power (15 W) on AMO removal efficiency were assessed in a batch photocatalytic reactor. Antibiotic concentration in output was measured by the spectrophotometer at the maximum wavelength of 280 nm. The optimum nano NiO dose was obtained to be 0.2 g/L. In this study, the removal efficiency decreased with increasing the concentration of AMO. Under optimal conditions of concentration, the removal efficiency was 96%. It was found that increasing the exposure time to UV increased the rate of AMO degradation in solution. The results also showed that the photo-degradation reaction approximately follows the pseudo-first-order kinetics with constant rates of 0.084, 0.074 and 0.046 min-1 for concentrations of 25, 50 and 100 mg/L, respectively. On the basis of the obtained results, it can be concluded that UV/NiO photocatalytic process can efficiently remove AMO from pharmaceutical wastewater.